Pre‐ and postoperative assessment of sinus grafting procedures using cone‐beam computed tomography compared with panoramic radiographs. Issue 5 (6th January 2012) - Baciut, Mihaela; Hedesiu, Mihaela; Bran, Simion; Jacobs, Reinhilde; Nackaerts, Olivia; Baciut, Grigore
Abstract Objectives The present study evaluated the clinical validity of cone‐beam computed tomography (CBCT) scans in comparison to panoramic radiographs regarding preoperative implant planning in combination with sinus grafting procedures. Materials and methods Preoperative assessment of the maxillary sinuses and implant planning using panoramic radiographs and CBCT scans was performed on 16 sinuses (13 patients) and comprised choice of treatment, timing of implant placement, sinus morphology, level of confidence, complication prediction and graft volume assessment. Six examiners were involved in the study. Results In the majority of cases there was a concordance between the treatment type based on either panoramic radiographs or CBCT. If any difference was found, this was due to an overestimation of bone quantity and quality on panoramic radiographs. The assessment of sinus morphology showed a significantly higher detection rate of sinus mucosal hypertrophy on CBCT. The most appealing result is a significant increase in surgical confidence and a significantly better prediction of complications when using CBCT. Conclusions A preoperative planning based on CBCT seems to improve sinus diagnostics and surgical confidence.